PROACTIVE METHODS OF BUILDING SAFETY IN CIVIL AVIATION (Perner's Contacts, 2011)
This paper focuses on building safety in current civil aviation with an emphasis on modern approaches. These modern approaches are primarily perception of safety as process before accident. The emphasis is on creating „Leading indicators“, that could be used as indicators before the undesirable outcomes of aviation such as serious incident or even accident has happened. Short summary of reactive approach is given to create wider knowledge base. Reactive approaches were very useful in the past to increase safety to ultra-safe level. But nowadays it is very crucial to implement proactive methods of building safety and give instruments to measure safety proactively before it is too late. Author calls this collection of tools and methods as Era of supervision mechanisms.
Keywords: aviation safety; creating safety; proactivity; safety indicators; measuring safety